Thermal characteristics of Falkner-Skan flow of time-dependent Maxwell material with varying viscosity and thermal conductivity - S. Bilal; Muhammad Yasir; Muhammad Bilal Riaz (International Journal of Thermofluids)
Thermosolutal attributes of Maxwell fluid over a riga wedge subjected to Falkner-Skan flow is described in current work. The effectiveness of the temperature-dependent viscosity and conductivity, along with the consideration of the radiative and activation energies, are included. Problem structuring is conceded into ODE's after utilizing similar variables on the PDE's. An efficient technique bvp4c in MATLAB is implemented to numerically tackle the nonlinear equations. Graphical outcomes are expressed for various involved factors by accounting three different wedge situations are illustrated i.e. λ = 0 (static), λ < 0 (shrinking) and λ > 0 (stretching). Wall drag, heat and mass gradients are also enumerated in comparative sense. Wide range of parameters are defined for instance, 0.3 ≤ A ≤ 0.7,  0.2 ≤ β ≤ 0.6,  0.5 ≤ M ≤ 1.5,  0.2 ≤ Bi ≤ 0.7,  0.5 ≤ m ≤ 1.3,  2.0 ≤ Pr ≤ 3.0,  0.3 ≤ Q ≤ 0.7,  and 0.2 ≤ Rd ≤ 0.6. The present study concludes that the velocity profile becomes progressive in the presence of larger values of the Deborah number and the unsteadiness parameter along the static, stretching, and shrinking wedges. The temperature profile shows the same elevating behavior corresponding to the radiation parameter and Biot number. The wall drag force is found to be reduced, and contrary aspects were noticed in the heat flux coefficient when the wedge is stretched compared to the other two cases.